Pemberdayaan Warga Binaan dalam Upaya Pencegahan TB Paru di Lapas Perempuan Kelas II A Pontianak - Ditha Astuti Purnamawati; Indah Dwi Rahayu; Lince Amelia Amelia; Dinarwulan Puspita (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Pulmonary Tuberculosis is a direct infectious disease caused by the tuberculosis germ (Mycobacterium tuberculosis) which is transmitted through the air (droplet nuclei) when a patient coughs and splashes of saliva containing the bacteria are inhaled by another person while breathing. The risk factors for the incidence of pulmonary TB are, occupancy density, lack of ventilation, poor lighting, access to inadequate facilities. The problems that exist in partners are the lack of counseling activities, especially related to health education on the prevention of pulmonary TB, the condition of densely populated prisons, inadequate ventilation and inadequate lighting are risk factors for the development of pulmonary TB. The first step is to collect pre-test data before being given health information on TB prevention. Furthermore, health education was given about prevention of pulmonary TB to the inmates. At the evaluation stage, post-test data were collected. Based on the results of community service activities with the target of assisted residents in the Pontianak class II women's correctional prison, it went well. Participants can participate in activities from start to finish with enthusiasm. After participating in this activity, it was found that there was an increase in knowledge in efforts to prevent pulmonary TB in prisons. It is hoped that the prison can increase health education activities, especially pulmonary TB, this is necessary to prevent transmission of pulmonary TB in prisons.